2023
DOI: 10.1021/acsmaterialslett.2c01065
|View full text |Cite
|
Sign up to set email alerts
|

Bimetal–Organic Frameworks for High Efficiency Catalytic Reduction

Abstract: The design of efficient reduction catalysts is crucial for sustainable development in order to reduce waste and protect the environment. Here, an ultrathin bimetallic metal–organic framework (MOF) is synthesized and fabricated as an effective catalyst for the reduction of 4-nitrophenol (which is harmful to the environment) to 4-aminophenol (which is an important chemical and pharmaceutical intermediate). The rapid reduction time of the as-prepared bimetallic CuNi-MOFs is 15 s, and the apparent rate constant is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…However, there are few types of MOF precursors used to synthesize excellent bimetallic spinels in the current research. 85,86 Meanwhile, in addition to the solvent method, coprecipitation and the reux method, there are also some synthetic methods of bimetallic MOFs that have not been used in the preparation of bimetallic spinels. 87,88 Furthermore, few researchers have explored the differences between the bimetallic spinels prepared by these different synthetic methods.…”
Section: Preparation Strategy Of the Mof-derived Bimetallic Spinelsmentioning
confidence: 99%
“…However, there are few types of MOF precursors used to synthesize excellent bimetallic spinels in the current research. 85,86 Meanwhile, in addition to the solvent method, coprecipitation and the reux method, there are also some synthetic methods of bimetallic MOFs that have not been used in the preparation of bimetallic spinels. 87,88 Furthermore, few researchers have explored the differences between the bimetallic spinels prepared by these different synthetic methods.…”
Section: Preparation Strategy Of the Mof-derived Bimetallic Spinelsmentioning
confidence: 99%
“…31 By doping Cu into the Ni-based MOF, effective electron accumulation was achieved in ultrathin bimetallic CuNi-MOF, significantly improving the catalytic activity toward 4-nitrophenol. 32 Furthermore, it has been demonstrated that the incorporation of an electron donating group (EDG) or electron withdrawing group (EWG) on ligands could introduce additional energy levels. 33 These energy levels are located between the intrinsic highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels, not only providing an efficient PET path to facilitate excited state migration on the framework, but also notably reducing the non-radiative decay.…”
Section: Introductionmentioning
confidence: 99%